Molecular and clinical epidemiology of carbapenem-resistant Enterobacterales in the USA (CRACKLE-2): a prospective cohort study. Issue 6 (June 2020) - van Duin, David; Arias, Cesar A; Komarow, Lauren; Chen, Liang; Hanson, Blake M; Weston, Gregory; Cober, Eric; Garner, Omai B; Jacob, Jesse T; Satlin, Michael J; Fries, Bettina C; Garcia-Diaz, Julia; et al.
Summary: Background: Carbapenem-resistant Enterobacterales (CRE) are a global threat. We aimed to describe the clinical and molecular characteristics of Centers for Disease Control and Prevention (CDC)-defined CRE in the USA. Methods: CRACKLE-2 is a prospective, multicentre, cohort study. Patients hospitalised in 49 US hospitals, with clinical cultures positive for CDC-defined CRE between April 30, 2016, and Aug 31, 2017, were included. There was no age exclusion. The primary outcome was desirability of outcome ranking (DOOR) at 30 days after index culture. Clinical data and bacteria were collected, and whole genome sequencing was done. This trial is registered with ClinicalTrials.gov, number NCT03646227 . Findings: 1040 patients with unique isolates were included, 449 (43%) with infection and 591 (57%) with colonisation. The CDC-defined CRE admission rate was 57 per 100 000 admissions (95% CI 45–71). Three subsets of CDC-defined CRE were identified: carbapenemase-producing Enterobacterales (618 [59%] of 1040), non-carbapenemase-producing Enterobacterales (194 [19%]), and unconfirmed CRE (228 [22%]; initially reported as CRE, but susceptible to carbapenems in two central laboratories). Klebsiella pneumoniae carbapenemase-producing clonal group 258 K pneumoniae was the most common carbapenemase-producing Enterobacterales. In 449 patients with CDC-defined CRE infections, DOOR outcomes were not significantly different in patients with carbapenemase-producing Enterobacterales, non-carbapenemase-producing Enterobacterales, and unconfirmed CRE. At 30 days 107 (24%, 95% CI 20–28) of these patients had died. Interpretation: Among patients with CDC-defined CRE, similar outcomes were observed among three subgroups, including the novel unconfirmed CRE group. CDC-defined CRE represent diverse bacteria, whose spread might not respond to interventions directed to carbapenemase-producing Enterobacterales. Funding: National Institutes of Health.